Lipedema: A Call to Action! - Buso, Giacomo (Obesity (Silver Spring), 2019)
Lipedema is a chronic progressive disease characterized by abnormal fat distribution resulting in disproportionate, painful limbs. It almost exclusively affects women, leading to considerable disability, daily functioning impairment, and psychosocial distress. Literature shows both scarce and conflicting data regarding its prevalence. Lipedema has been considered a rare entity by several authors, though it may be a far more frequent condition than thought. Despite the clinical impact on women's health, lipedema is in fact mostly unknown, underdiagnosed, and too often misdiagnosed with other similarly presenting diseases. Polygenic susceptibility combined with hormonal, microvascular, and lymphatic disorders may be partly responsible for its development. Furthermore, consistent information on lipedema pathophysiology is still lacking, and an etiological treatment is not yet available. Weight loss measures exhibit minimal effect on the abnormal body fat distribution, resulting in eating disorders, increased obesity risk, depression, and other psychological complaints. Surgical techniques, such as liposuction and excisional lipectomy, represent therapeutic options in selected cases. This review aims to outline current evidence regarding lipedema epidemiology, pathophysiology, clinical presentation, differential diagnosis, and management. Increased awareness and a better understanding of its clinical presentation and pathophysiology are warranted to enable clinicians to diagnose and treat affected patients at an earlier stage.